Development of Normoxic Polymer Gel Dosimeters Based On Hydroxyethylacrylate And Hydroxyethylmethacrylate Monomers and Their Characterizations Using Raman Spectroscopy and Magnetic Resonance Imaging Scanner - Abdul Rahman, Azhar (2009)
Polymer gel dosimeters in conjunction with the nuclear magnetic resonance imaging (MRI) are potentially useful for verification of complex dose distributions in three dimensions (3D) applied in radiotherapy treatment planning. The radiation-induced normoxic polymer gels of polyhydroxyethylacrylate (PHEAG) and polyhydroxyethylmethacrylate (PHEMAG) have been studied using Raman spectroscopy and MRI scanner. The studies are focused on PHEAG and PHEMAG because these monomers belong to acrylic group. Most of the monomer in the acrylic group will indicate physical changes dramatically due to radiation given. The PHEAG and PHEMAG were synthesized from 2-hdroxyethylacrylate (HEA) and hydroxyethylmethacrylate (HEMA) monomer (2 to 5% w/w) respectively and together with methylene-bis-acrylamide (BIS) crosslinker (1 to 4% w/w), gelatine (3% w/w), ascorbic acid (5 mM to 15 mM) and completed with de-ionized water. The dosimeters were irradiated with 60Co teletherapy γ-rays source at a constant dose rate of 0.177 Gy/min, receiving doses up 20 Gy for the single point dose measurement and the 3D dose distributions scanning. The polymerization intended for PHEMAG was followed by the change of Raman intensity at Raman shift of 812 cm-1, 1978 cm-1 and 2885 cm-1 assigned for C-C stretching, C=O stretching and CH3 stretching respectively and at 812 cm-1 assigned for C-C stretching in favour of PHEAG. The Raman intensity y corresponding to the amount of polymer formed in both PHEAG and PHEMAG increases with increasing dose D and follows a mono-exponential equation given as ( / 0 ) 0 y = y + A1− e−D D . The dose sensitivity 0 D derived from the equation and k factor derived from a linear relationship between 0 D and co-monomer concentration were found increasing with the increase of initial concentrations of monomer, cross-linker and anti-oxidant. The consumptions of co-monomers in PHEAG were studied by a decrease intensity of C=C stretching at 2887 cm-1 and 2602 cm-1 of HEA and BIS respectively and at 2602 cm-1 and 2369 cm-1 of HEMA and BIS respectively in favour of PHEMAG. The intensity decreases with increasing dose and follows mono-exponential equation given as ( / 0 ) 0 y = y − A1− e−D D . The dose sensitivity 0 D and k factor were also found to increase with the increase of monomer, cross-linker and anti-oxidant concentrations. The PHEMAG phantoms synthesized from HEMA monomer (3% w/w), BIS crosslinker (2 to 4% w/w), gelatine (3%), anti-oxygen ascorbic acid (15 mM to 55 mM) and completed with de-ionized water were exposed with single and crossed beams to simulate radiotherapy treatment. Magnetic resonance imaging (MRI) scanner was used to scan dose distribution of the phantoms and the 3D images were evaluated using a digital densitometer. It was found that the absorbed dose decreases with the increase of depth dose inside the phantom and the consequently two crossed beams of 20 Gy each produced less than 35 Gy beyond 3 cm depth dose. There is a slightly increase in dose with the increase of ascorbic acid concentration for all the radiation beams tested, indicating the use of ascorbic acid alone as anti-oxidant agent in PHEMAG was able to produce normoxic polymer gel dosimeters. Referring to the results of dose correlation factor k, it can be concluded that kHEMA is more significant than kHEA.